Anna and the French kiss - Perkins, Stephanie (New York : SPEAK, 2010)
"Anna is looking forward to her senior year in Atlanta, where she has a great job, a loyal best friend, and a crush on the verge of becoming more. Which is why she is less than thrilled about being shipped off to boarding school in Paris - until she meets Etienne St. Clair: perfect, Parisian (and English and American, which makes for a swoon-worthy accent), and utterly irresistible. The only problem is that he's taken, and Anna might be, too, if anything comes of her almost-relationship back home. As winter melts into spring, will a year of romantic near - misses end with the French kiss Anna - and readers - have long awaited?" --From the publisher.
Keywords: Interpersonal relations -- Fiction; Infatuation -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Foreign study -- Fiction; Paris (France) -- Fiction; France -- Fiction